2019
DOI: 10.14393/bj-v35n2a20198-41747
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of methodology for conducting germination test in forage pea seeds

Abstract: Seeds presents variable germination performance at different temperatures and substrates, which are basic components of germination test. Within this context, this work aimed to adapt the methodology for the seeds germination's test of P. sativum subsp. arvense. The experiment required four portions of seeds, five temperature degrees (15, 20, 25, 20-30 and 15-25 °C), and two substrata (roll of paper and in sand). Seeds evaluation considered the following: moisture degree and germination test. The effect of see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…This was also used to evaluate germination of citrus rootstock cultivars (SARMIENTO et al, 2016). The best germination performance in paper substrate can be attributed to the vegetative structure's development lower physical impairment and higher aeration of this substrate in comparison to sand (MACHADO et al, 2019). Use of sand causes difficulties in maintaining the sterile laboratory environment, in addition to difficulties in obtaining, storing, disposing and reusing it, recommendations described in the BRASiL (2009).…”
Section: Resultsmentioning
confidence: 99%
“…This was also used to evaluate germination of citrus rootstock cultivars (SARMIENTO et al, 2016). The best germination performance in paper substrate can be attributed to the vegetative structure's development lower physical impairment and higher aeration of this substrate in comparison to sand (MACHADO et al, 2019). Use of sand causes difficulties in maintaining the sterile laboratory environment, in addition to difficulties in obtaining, storing, disposing and reusing it, recommendations described in the BRASiL (2009).…”
Section: Resultsmentioning
confidence: 99%
“…The counts were performed daily until 14 days after sowing, when the percentage of seedling emergence in the field was calculated according to Nakagawa (1994). Emergence first count of seedlings in the field: emerged seedlings were counted when they represented 50 ± 1 % of the final emergence (MACHADO et al, 2019). Emergence speed index of seedlings in the field: calculated from the data of daily counts of emerged seedlings in the emergence test and determined using the formula proposed by Maguire (1962).…”
Section: Methodsmentioning
confidence: 99%
“…Germination: conducted on a paper roll substrate, moistened with a water volume equivalent to 2.5 times the weight of the dry substrate, and placed in a biochemical oxygen demand germination chamber at 20 °C. The percentage of normal and abnormal seedlings was determined on the seventh day after sowing (MACHADO et al, 2019). To maintain substrate moisture, the rolls with the seeds were placed in plastic bags (COIMBRA et al 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, a study by R. C. da, Grzybowski and Panobianco (2016) with maize seeds reported that, depending on the substrate, higher and lower vigor lots could show similar performances, proving that the substrate has a greater effect on the results than the physiological quality of the seeds in germination and seedling vigor tests. However, there have also been reports that high vigor fodder pea and safflower lots were less demanding on substrate conditions than low vigor lots (Gama et al, 2019;Machado, Martins, Silva Cruz, Assis, 2019b).…”
Section: Germination and First Count Testmentioning
confidence: 99%